Functional alignment is a feasible alignment strategy in robotic assisted total knee arthroplasty for knee osteoarthritis with extra-articular deformity – A case series - Eu Wei Cheong; Yuik Ho Jade Pei; Kunalan G. (SICOT-J)
Introduction: Extraarticular deformity (EAD) with knee arthritis is a complex condition involving tri-planar bone deformity with pathological malalignment and chronic soft tissue contracture or laxity in the knee joint. Intraarticular correction by TKA, which was previously performed with conventional manual jig by mechanical alignment technique, had its limits and difficulties especially extensive soft tissue release and risk of jeopardizing the collateral ligaments. Robotic technology allows for reproducible and precise execution of surgical plan and allows adjustment to various new personalised alignment philosophy including functional alignment (FA). FA technique involves the adjustment of components positioning that least compromise the soft tissue envelope while restoring the limb alignment and joint obliquity to create a balanced knee. The aim is to study the outcome of intra-articular correction by robotic assisted TKA using Functional Alignment (FA) technique. Methodology: This is a single surgeon series of 8 patients with extraarticular deformity who underwent robotic assisted total knee arthroplasty (TKA) with FA technique. Soft tissue release was gradually released and followed by adjustments of implant positioning in order to achieve a balanced medio-lateral gap. Results: Postoperatively, the lower limb alignment of all patients were restored within 6° (mean 4.54°) based on functional alignment boundaries. Knee phenotype and joint line obliquity (JLO) were restored in comparison to contralateral lower limb. There were 6 varus and 2 valgus malalignment. 7 patients were implanted with posterior stabilized implants while 1 was implanted with cruciate retaining implant. Arc of knee flexion and extension improved (P = 0.002). There was a large postoperative improvement in the Knee Society Score (KSS) (P < 0.001). Discussion: Intraarticular correction by TKA for EAD with knee arthritis is technically reliable with robotic technology. It allows intraoperative adjustment following functional alignment philosophy, thereby, restoring pre-arthritic alignment, knee phenotype and joint line obliquity.